استراتيجية التعلم التعاوني ودورها في تنمية التفكير الابداعي والتفوق المدرسي لدى تلاميذ التعليم الابتدائي - الأشهب, عبد السلام; مقدود, البشير (University of Eloued جامعة الوادي, 2020)
يعتبر أسلوب التعلم التعاوني أحد البدائل للتعامل الصفي الجماعي، ويمكن تطبيقه لكل الأعمار وجميع المستويات. لا شك أن عملية جمع عدد كبير من التلاميذ وتعليمهم في آن واحد اقتصاد في الجهود والنفقات، ولكن هذا يكون على حساب مراعاة الفروق الفردية التي يتم تجاهلها رغم وجودها في الذكاء والميول والاستعداد والقدرة على التعبير والخلفيات الاجتماعية والثقافية. ومن الجدير بالذكر أن هناك الكثير من الدراسات التي تشير إلى أن التلاميذ على اختلاف قدراتهم يصبحون أكثر اهتماماً بمهماتهم التعليمية إذا كانت المجموعات متفاعلة مع بعضها البعض, كما أن اتجاهاتهم نحو المدرسة والنظام يصبح أكثر ايجابية, ودراستنا سوف تتناول استراتيجية التعلم التعاوني ودورها في تنمية التفكير الابداعي والتفوق المدرسي لدى تلاميذ التعليم الابتدائي Abstract : Cooperative learning is one of the alternatives to collective classroom therapy and can be applied to all ages and levels. There is no doubt that the process of bringing together a large number of students and teaching them at the same time an economy in the effort and expenditure, but this is at the expense of taking into account the individual differences that are ignored, despite their presence in intelligence and tendencies and readiness and ability to express social and cultural backgrounds. It should be noted that there are many studies that indicate that students of different abilities become more interested in their educational tasks if the groups interact with each other, and their attitudes towards school and the system becomes more positive , Our study will address the cooperative learning strategy and its role in the development of creative thinking and scholastic excellence among primary school students.
The cooperative learning strategy and its role in developing creative thinking and school excellence among primary education students.
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: التعلم التعاوني، التفكير الابداعي، التفوق المدرسي، مرحلة التعليم الابتدائي; collaborative learning , creative thinking , school excellence , the stage of primary education